Majority think UK government COVID-19 response worse than other developed countries, almost half say response too focused on protecting the economy - Fletcher, R; Kalogeropoulos, A; Nielsen, R (Reuters Institute for the Study of Journalism, 2020)
In this RISJ Factsheet we examine how people think about the coronavirus pandemic in the UK and how different institutions in the UK have responded to it. This is the seventh in a series of ten factsheets based on an ongoing online panel survey of a representative sample of the UK population, fielded from 2 July to 8 July 2020. We find that: (i) a majority (57%) of the public say they think the UK government’s response to the coronavirus pandemic has been worse than most other developed countries (up from 46% in late April), (ii) almost half (44%) feel that the government response is too focused on protecting the economy (up from 19%), but (iii) perception of news media coverage of the government is largely unchanged, with one third (33%) saying the coverage has not been critical enough, 26% too critical, and 28% saying coverage has been fair.